Raising Student Engagement through âInstagramâ - Jatmiko, Puguh (Sebelas Maret University, 2016)
The study was to examine if an Instagram post could help to raise studentsâ engagement towards a certain topic. The first step was to introduce and discuss with the students a topic in the class. The students were then asked to find more information about the topic at home, and when they found any, they were asked to post it on their Instagram accounts with a certain hashtag. Once students posted pictures on Instagram, they then were asked to give comments to each otherâs posts. The aspects explored were the studentâs engagement and involvement in a discussion off the class, while they were away from the school. Upon completion of the study, I found that there were more students engaged in the discussion; this was shown by the number of pictures the students posted on Instagram. This study offered another option for teachers to help students review and get ready for the next class.Â